# 若干常见的傅里叶级数

Eufisky posted @ 2014年4月10日 17:45 in 数学分析 , 1469 阅读

\begin{align*}&x = \frac{\pi }{2} - \frac{4}{\pi }\sum\limits_{n = 1}^\infty  {\frac{{\cos \left[ {\left( {2n - 1} \right)x} \right]}}{{{{\left( {2n - 1} \right)}^2}}}}  = 2\sum\limits_{n = 1}^\infty  {{{\left( { - 1} \right)}^{n - 1}}\frac{{\sin \left( {nx} \right)}}{n}} \qquad 0 \le x < \pi \\&{x^2}=\frac{{{\pi ^2}}}{3}+4\sum\limits_{n = 1}^\infty  {{{\left( { - 1} \right)}^n}\frac{{\cos \left( {nx} \right)}}{{{n^2}}}} \qquad - \pi  \le x \le \pi \\&\cos \left( {ax} \right) = \frac{{\sin \left( {a\pi } \right)}}{\pi }\left( {\frac{1}{a} + \sum\limits_{n = 1}^\infty  {{{\left( { - 1} \right)}^n}\frac{{2a}}{{{a^2} - {n^2}}}\cos \left( {nx} \right)} } \right)\qquad - \pi  \le x \le \pi \\&\cot x = \frac{1}{x} + \sum\limits_{n = 1}^\infty  {\frac{{2x}}{{{x^2} - {n^2}{\pi ^2}}}}\qquad x \ne k\pi ,k = 0, \pm 1, \pm 2, \cdots \\&\frac{1}{{\sin x}} = \frac{1}{x} + \sum\limits_{n = 1}^\infty  {{{\left( { - 1} \right)}^n}\frac{{2x}}{{{x^2} - {n^2}{\pi ^2}}}} \qquad x \ne k\pi ,k = 0, \pm 1, \pm 2, \cdots \\&\left| {\cos x} \right| = \frac{2}{\pi } + \frac{4}{\pi }\sum\limits_{n = 1}^\infty  {\frac{{{{\left( { - 1} \right)}^{n + 1}}}}{{4{n^2} - 1}}\cos \left[ {\left( {2n} \right)x} \right]} \qquad x \in \left( { - \infty , + \infty } \right)\\&\left| {\sin x} \right| = \frac{2}{\pi } - \frac{4}{\pi }\sum\limits_{n = 1}^\infty  {\frac{1}{{4{n^2} - 1}}\cos \left[ {\left( {2n} \right)x} \right]} \qquad x \in \left( { - \infty , + \infty } \right)\\&\sum\limits_{n = 1}^\infty  {{{\left( { - 1} \right)}^{n - 1}}\frac{{\cos \left( {nx} \right)}}{n}}  = \ln \left( {2\cos \frac{x}{2}} \right)\qquad - \pi  < x < \pi \\&\sum\limits_{n = 1}^\infty  {\frac{{\cos \left( {nx} \right)}}{n}}  =  - \ln \left( {2\sin \frac{x}{2}} \right)\qquad 0 < x < 2\pi \\&{e^{ax}} = \frac{{{e^{2a\pi }} - 1}}{\pi }\left( {\frac{1}{{2a}} + \sum\limits_{k = 1}^\infty  {\frac{{a\cos kx - k\sin kx}}{{{k^2} + {a^2}}}} } \right)\qquad x \in \left( {0,2\pi } \right),a \ne 0\end{align*}

${e^{ax}} = \frac{{{e^{2a\pi }} - 1}}{\pi }\left( {\frac{1}{{2a}} + \sum\limits_{n = 1}^\infty {\frac{{a{\mathop{\rm cosn}\nolimits} x - n{\mathop{\rm sinn}\nolimits} x}}{{{n^2} + {a^2}}}} } \right)\quad \;\;\;{\mkern 1mu} x \in \left( {0,2\pi } \right),a \ne 0$

$\widetilde{f}(0)=\widetilde{f}(2\pi)=\frac{f(2\pi-0)+f(0+0)}{2}=\frac{e^{2\pi a}+e^{0\cdot a}}{2}=\frac{e^{2\pi a}+1}{2}.$

$\widetilde{f}(x)= \frac{{{e^{2a\pi }} - 1}}{\pi }\left( {\frac{1}{{2a}} + \sum\limits_{n = 1}^\infty{\frac{{a{\mathop{\rm cosn}\nolimits} x - n{\mathop{\rm sinn}\nolimits} x}}{{{n^2} + {a^2}}}} } \right)\qquad {\mkern 1mu} - \infty < x < + \infty$

$\frac{{{e^{2\pi }} + 1}}{2} = \frac{{{e^{2\pi }} - 1}}{\pi }\left( {\frac{1}{2} + \sum\limits_{n = 1}^\infty {\frac{1}{{{n^2} + 1}}} } \right).$
$\sum\limits_{n = 1}^\infty {\frac{1}{{{n^2} + 1}}} = \frac{{{e^{2\pi }} + 1}}{2} \cdot \frac{\pi }{{{e^{2\pi }} - 1}} - \frac{1}{2} = \frac{\pi }{2}\frac{{{e^{2\pi }} + 1}}{{{e^{2\pi }} - 1}} - \frac{1}{2}.$

$\sum\limits_{n = 1}^\infty {\frac{1}{{{n^2} + {a^2}}}} = \frac{\pi }{{2a}}\frac{{{e^{2\pi }} + 1}}{{{e^{2a\pi }} - 1}} - \frac{1}{{2{a^2}}}.$

(输入验证码)
or Ctrl+Enter